2020
DOI: 10.1111/all.14529
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the conversion between specific IgE test platforms for nut allergens in children and adolescents

Abstract: Background Multiplex tests allow for measurement of allergen‐specific IgE responses to multiple extracts and molecular allergens and have several advantages for large cohort studies. Due to significant methodological differences, test systems are difficult to integrate in meta‐analyses/systematic reviews since there is a lack of datasets with direct comparison. We aimed to create models for statistical integration of allergen‐specific IgE to peanut/tree nut allergens from three IgE test platforms. Methods Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
11
2
Order By: Relevance
“…The availabilities of single allergens and advanced microarray technology have made it possible to obtain a quick insight into the sensitization profile of a patient ( 210 ). In order to enable quantitative conversion between different multiplex IgE test-platforms for nut allergens, statistical models have been established recently ( 211 ). For the European MeDALL research project, an allergen chip with 170 allergen molecules, including natural purified and recombinant allergens from almond, cashew, pistachio and peanut, was developed which could be used even for dried blood samples ( 212 ).…”
Section: Diagnosis Of Nut Allergymentioning
confidence: 99%
“…The availabilities of single allergens and advanced microarray technology have made it possible to obtain a quick insight into the sensitization profile of a patient ( 210 ). In order to enable quantitative conversion between different multiplex IgE test-platforms for nut allergens, statistical models have been established recently ( 211 ). For the European MeDALL research project, an allergen chip with 170 allergen molecules, including natural purified and recombinant allergens from almond, cashew, pistachio and peanut, was developed which could be used even for dried blood samples ( 212 ).…”
Section: Diagnosis Of Nut Allergymentioning
confidence: 99%
“…Spearman correlations with ImmunoCAP exceeded 0.9 for Timothy grass and birch and also for most of the major component allergens. The EUROLINE was also used as a comparator in the previously mentioned study by Hoang et al 41 The key finding was that the EUROLINE reported more positive sensitizations to certain allergens, including hen's egg, cow's milk, and almond than either ALEX or the ISAC-related MeDALL chip. This may well be explained by the fact that the amount of allergen on the solid phase is greater for the immunoblot-based EUROLINE than for the microarray assays.…”
Section: Studies That Investigated Other Multiplex Assaysmentioning
confidence: 99%
“…To our knowledge, no plant-produced recombinant allergen is used in any of the commercially available singleplex or multiplex diagnostic assays. Molecular allergy diagnosis of peanut allergy is performed with either natural or E. coli -produced rAra h 2 in the singleplex ImmunoCAP (r) assay (Park et al, 2018 ) and in multiplex assays, such as the ImmunoCAP ISAC (r) (Gadisseur et al, 2011 ), the experimental MeDALL-chip (n) (Lupinek et al, 2014 ), or the ALEX allergy explorer (r) (Hoang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%